Two-surgeon technique of parenchymal transection contributes to reduced transfusion rate in patients undergoing major hepatectomy - Palavecino, Martin (2010)
Background Blood transfusions are an independent risk factor for adverse outcomes after hepatectomy. In-hospital transfusions are still reported in one third of patients in major series. Data on factors affecting blood transfusions in large series of liver resection are limited. The aim of this study was to evaluate factors predictive of blood transfusion in hepatectomies performed at a tertiary referral center. Methods Records of 1,477 patients who underwent 1,557 liver resections between 1998 and 2007 were reviewed. Multivariate analysis of risk factors for red cell transfusion was performed. Results Median intra-operative blood loss was 250 cc, and 30-day peri-operative red cell transfusion rate was 27%. On multivariate analysis, factors that significantly predicted increased red cell transfusion rates were female sex, pre-operative hematocrit <30%, platelet count <100,000/mm3, simultaneous resection of other organs, major hepatic resection, use of the Pringle maneuver, and tumors >10 cm. Parenchymal transection technique was an independent risk factor for perioperative red cell transfusion; the usage of the 2-surgeon technique (combined saline-linked cautery and ultrasonic dissection) was associated with a lower transfusion rate than other techniques, including ultrasonic dissection alone, finger fracture, and stapling (P < .001). Conclusion Although most factors that affect the red cell transfusion rate for liver resection are patient- or tumor-related, the parenchymal transection technique is under the surgeon's control. The decrease in transfusion rate associated with the use of the 2-surgeon technique emphasizes the important role of the hepatobiliary surgeon in determining outcomes after liver resection. Liver resection is the treatment of choice for primary and secondary malignant tumors and benign tumors based on well-defined criteria. Liver resection has been used increasingly in the last 20 years, and mortality rates associated with the procedure are less than 5% at high-volume centers.1, 2 and 3 The safety of liver resection is in part the result of the development of techniques aimed at reducing blood loss. Despite these improvements, blood transfusion is still reported in more than one third of patients who undergo liver resection.4, 5, 6 and 7 These high rates of blood transfusion are likely associated with patient and tumor factors. Although transfusion rates can be reduced to almost 0 in uncomplicated hepatectomies, the blood transfusion rates associated with liver resection remain significant at tertiary referral centers, such as ours. This difference is because patients treated at such centers often present with large tumor size,8 underlying liver disease,9 and chemotherapy-associated hepatic toxicity.10 In an effort to reduce the need for blood transfusions in patients undergoing liver resection, we developed a 2-surgeon technique to optimize parenchymal transection.11 In our preliminary series,11 the combined use of saline-linked cautery and ultrasonic dissection was shown to be safe and to reduce blood loss, operation time, and time of inflow occlusion. The objective of this study was to evaluate, in our experience over a 10-year period, factors predictive of blood transfusion in patients who underwent liver resection. Further, we evaluated the effect of the increasing use of the 2-surgeon technique for parenchymal transection on the blood transfusion rate.